ECONOMIC AND LEGAL RELATIONS BETWEEN THE AUTHOR AND THE EMPLOYER / CUSTOMER (Economics and region, 2021)
The total value of all transactions in the intellectual property market is a reflection of the economic condition of this market. The system forming is the primary transaction of alienation of property rights from the creator to the employer to use the result of intellectual, creative activity in business. Without adherence to the exact economic content of this primary transaction, it is impossible for the state to obtain a proper economic result. The purpose of the article is to identify the European economic structure of legal relations between creators-employees and employers through the prism of national laws, other regulations and international treaties, the consent of which is given by the Verkhovna Rada of Ukraine, as a part of national legislation of Ukraine.
Keywords: economic system; intellectual property; intellectual product; copyright; intangible asset; intellectual property market; patent law; institutions of intellectual property protection